ANALYZING THE EFFECT OF STOCK MARKET CAPITALIZATION AND FINANCIAL TECHNOLOGY ADOPTION ON BANK PROFITABILITY - Elmira Siska; Taat Kuspriyono; Dante Rio Sebastian (Jurnal Apresiasi Ekonomi, 2023)
The main objective of this research is to examine how stock market capitalization and the adoption of financial technology services affect on banking profitability. This study used a quantitative-descriptive research design with the research strategy adopted is a case study at Bank Central Asia (BCA). This study utilized the secondary data in an annual time series format spanning from 2017 to 2021. The return on Asset (ROA) of BCA as a proxy of bank profitability is a dependent variable. Whereas the stock market capitalization and value transaction of mobile banking and internet banking is the proxy of financial technology services as the independent variables. Program SPSS version 26 was employed to process the data for performing the Classical Assumption Test, the Multiple Linear Regression, the t-Test, and the Coefficient of Determination Test. The findings of current research prove that stock market capitalization and the adoption of financial technology service has a positive and significant impact on BCA’s profitability.  This finding indicates that profitability increases with an increase in capitalization and enhance the adoption of financial technology service by the bank.